National Strategies of Ophthalmic Education in Iran - B Einollahi; MA Javadi; A Entezari (Tehran University of Medical Sciences, 2012)
Background: Academic medicine is in a state of dramatic transformation. For this reason strategic thinking is the most essential part of educational planning. The main purpose of the present study was developing the strategic educational planning of Ophthalmology in Iran from 2007 to 2010Methods: A qualitative investigation using focus group discussion has been implemented successfully for developing educational planning. Six to twelve representatives of key stakeholders in the ophthalmic education of Iran participated to this study.Results: Strengths, weaknesses, opportunities and threats of ophthalmology education in Iran were analyzed. Strategic goals in education, research, and health service providing domains were being developed. Educational goals were defined as training of human resources in accordance with the community needs at the level of general practitioner, specialist, and fellowships in ophthalmology. Research goals of the program were defined as scientific inter-departmental and international communications, in order to promote the level of education, research, and treatment in the country. Also, in the field of health services according to the community needs, providing services by the means of advanced and cost effective methods were defined as strategic objectives.Conclusion: Based on this strategic plan in the last three years ophthalmic education in Iran shall be many changes in educational, research and health care provision for social accountability.